Toward an Efficient Differentiation of Two Diaporthe Strains Through Mass Spectrometry for Fungal Biotyping - Kathleen Hernández-Torres; Daniel Torres-Mendoza; Gesabel Navarro-Velasco; Luis Cubilla-Rios (Current Issues in Molecular Biology)
Considering that fungi display a great morphological, ecological, metabolic, and phylogenetic diversity, their taxonomic identification is extremely important because it helps us establish important information about each species and its possible biochemical and ecological roles. Traditionally, the identification of fungi at the species level has been carried out with molecular tools such as DNA sequencing, but it still represents a huge challenge today due to the heterogeneity of the fungal kingdom, making the task of identification a complex and difficult process. Biotyping, a type of chemotaxonomy, has been developed in the field of the identification/differentiation and classification of micro-fungi through tools such as mass spectrometry (MS). Here, two endophytic strains isolated from two different hosts were cultivated and studied regarding their morphology and molecular biology. Morphology analysis determined the strains as Diaporthe, and the molecular analysis results grouped them as D. melongenae. We sought a faster and less complex way of differentiating these fungal strains of interest through an MS chemical profile and MS/MS data using a low-resolution mass spectrometer. Additionally, we linked this information with the structure of compounds previously isolated in the genus Diaporthe. Studies conducted using this technique allowed us to propose the structure of distinctive molecules that are unique to each strain and share compounds common to this genus (13 compounds in total). In addition, this is the first report of secondary metabolites in D. melongenae. The dataset demonstrates that the two strains under investigation can be distinguished via mass spectrometry, suggesting host affinity; both exhibits pronounced differences in their chemical profiles across all culture media and incubation periods with the parameters described herein.